A Systematic Review of Multilevel Influenced Risk-Taking in Helicopter and Small Airplane Normal Operations - Harris, Matt R.; Fein, Erich C.; Machin, M. Anthony (Frontiers in Public Health, 2022)
The violation of aviation rules, particularly meteorological flight rules, can have fatal outcomes. Violation can sometimes be explained by intentional risk-taking, alternatively it can be the manifestation of a strategy to enhance performance and influence outcomes, such as saving time or fulfilling customer expectations. The aim of this study was to determine the types of risk-taking behaviour within extant empirical research and identify multilevel antecedents related to risk-taking in the context of aviation operations, via a systematic literature review. 4,742 records were identified, which after screening resulted in the detailed consideration of 10 studies, three qualitative and seven quantitative studies, which met the eligibility criteria. Only published works were included in the review, thus the results may have been subject to publication bias, however, the types of risk taking within the research were consistent with that observed in Australian and New Zealand accident reports. The predominate risk-taking behaviour was that of continuing Visual Flight Rules (VFR) flight into deteriorating conditions / Instrument Meteorological Conditions (IMC). Multilevel influences could be categorised under two overarching themes, being ‘continuation influence’ and ‘acceptance of risk / normalisation of deviance’. One or both themes was consistently observed across the finding in all studies, although precaution should be given to the relative frequency of the reported associations. This review indicates the value of considering the social and organisational influences on risk-taking, and suggests avenues for future research, in particular exploring the influences through a Self-Determination Theory (SDT) lens.